Adsorption and desorption of methyl orange dye on environmentally aged polyethylene, polyethylene terephthalate and polystyrene microplastics in aquatic environment - Ahsan Habib; Sayedunnesa Nishi; Md. Muhaiminul Haque; Md. Tauhiduzzaman; Kobita Khatun; Mst Shamima Akter; Esrat Sultana; Tapos Kumar Chakraborty; Samina Zaman; Gopal Chandra Ghosh (PLoS ONE, 2025)
This study investigated the adsorption of methyl orange (MO), an anionic dye, on environmentally aged polyethylene (PE), polyethylene terephthalate (PET), and polystyrene (PS) microplastics (MPs) to understand their interactions in aquatic environments. The MPs were characterized using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The adsorption experiment data followed pseudo-second-order kinetics and fit well with the Langmuir and Freundlich isotherm models. The adsorption capacities of MO onto the MPs were 2.86 mg/g, 3.64 mg/g, and 3.81 mg/g for PE, PET, and PS, respectively, at a neutral pH of 7.0. The MPs combined with MO mainly through chemisorption, hydrogen bonding, and hydrophilic interaction. The optimum conditions for MO (23.41% for PE, 22.8% for PET, and 22.64% for PS) removal by the MPs were: pH 2, MO concentration of 27.5 mg/L, and MPs dose of 15.0 g/L, as determined using response surface methodology (RSM). Additionally, the presence of salt (NaCl) and humic acid (HA) competed with MO for adsorption sites on the MPs. The desorption of MO from the MPs was relatively higher in freshwater (16–30%) than in simulated seawater (12–19%). This study elucidates the interaction of MO with environmentally aged PE, PET, and PS MPs in aquatic environments, and demonstrates the transport capacity of MO dye from wastewater to freshwater, and eventually to the ocean.